PENGARUH DISIPLIN KERJA DAN KOMITMEN ORGANISASI KARYAWAN PT. CILIANDRA PERKASA DESA BANDUR PICAK KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR PROVINSI RIAU - Nurhayana, Nurhayana; Sri Dewi, Diana (Komunitas Manajemen Kompetitif, 2025)
This study aims to examine the influence of organizational culture on employee engagement among Secretariat employees of the Regional People's Representative Council (DPRD) in regencies and cities across Riau Province. The research is expected to provide both theoretical contributions to the development of management science particularly in the areas of organizational behavior and human resource management and practical benefits for improving employee engagement in public institutions. The population of the study consists of 589 employees, from which a sample of 239 respondents was determined using the Slovin formula. Data analysis was conducted using Structural Equation Modeling (SEM). The results indicate that organizational culture has a positive and significant influence on employee engagement. These findings highlight the strategic importance of fostering a strong organizational culture to enhance employee attachment, commitment, and involvement in the public sector context. Keywords: Organizational Culture, Employee Engagement